Perancangan Helpdesk Sistem Model Berbasis Itil Versi 3 Domain Problem Management Dan Incident Management - Ali Imron; Widya Cholil; Linda Atika (Jurnal Informatika Global)
AbstractThe management of information technology service management at this time is very influential for the organization in achieving its strategic objectives. A large ITIL collection of best practices, tools and methods used in the management and handling of IT services. In this paper, the emphasis will be placed on the Operations Services field at ITIL on the incident management process used to manage the IT incident life cycle. The main idea is to find solutions for optimal planning of interventions that are automated in the incident management process. Indeed, despite the number of software solutions for the incident management process, intervention planning is still the user's task due to the high complexity of its automation. In this paper, we propose two solutions for optimal automated planning of interventions in incident management. The first is inspired by vehicle routing problems and the second is inspired by obstacle-based problems. Finally, we will compare the results of the two solutions. This research will analyze and design the service problems that occur in seconds by using the domain problem management and incident management contained in the service operation which is a sub domain of ITIL. ITIL in the concept of research data collection using interviews and literature studies, in which the data generated from this method there are several incidents that often occur in seconds, so that will be presented a result. System helpdesk that will provide a conclusion of several incidents that often occur and are complained of by system users. From the results of the incident that occurred, it will be carried out according to the flow of the helpdesk that has been built and if an incident occurs repeatedly, it will become a management problem.Keywords :  ITIL, IT design, problem management, incident management, and service operationAbstrakPengendalian manajemen pelayanan teknologi informasi pada saat ini sangat berpengaruh untuk organisasi dalam mencapai tujuan strateginya. Sekumpulan ITIL besar praktik, alat, dan metode terbaik yang digunakan dalam pengelolaan dan penanganan layanan TI. Dalam tulisan ini, akan menempatkan penekanan pada field Layanan Operasi di ITIL pada proses manajemen insiden yang digunakan untuk mengelola siklus hidup insiden TI. Gagasan utamanya adalah menemukan solusi untuk perencanaan optimal intervensi yang otomatis dalam proses manajemen insiden. Memang, meskipun jumlah solusi perangkat lunak untuk proses manajemen insiden, perencanaan intervensi masih merupakan tugas pengguna karena kompleksitas tinggi otomatisasi nya. Dalam tulisan ini, kami mengusulkan dua solusi untuk perencanaan optimal otomatis intervensi dalam pengelolaan insiden. Yang pertama terinspirasi oleh masalah perutean kendaraan dan yang kedua terinspirasi oleh masalah berbasis kendala. Akhirnya, kita akan membandingkan antara hasil dua solusi tersebut.Penelitian ini akan menganalisa dan melakukan desain perancangan terhadap masalah pelayanan yang terjadi pada detik sumsel dengan menggunakan domain problem management dan incident management yang terdapat pada service operation yang merupakan sub domain dari ITIL.  ITIL  dalam konsep penelitian pengumpulan data menggunakan metode wawancara dan studi literatur, yang mana data yang dihasilkan dari metode ini terdapat beberapa insiden yang sering terjadi pada detik sumsel, sehingga akan disajikan sebuah hasil. Helpdesk sistem yang akan memberikan sebuah kesimpulan dari beberapa insiden yang sering terjadi dan dikeluhkan oleh pengguna sistem. Dari hasil insiden yang terjadi maka akan dilakukan sebuah penanganan sesuai alur dari helpdesk yang telah dibangun dan jika sebuah insiden terjadi berulang kali maka semua itu akan dijadikan sebuah problem management.Kata kunci :  ITIL, desain TI, problem management,  incident managemant,  dan service operation